A contextual semantic representation of learning assets in online communities of practice. (1st January 2013) - Berkani, Lamia; Chikh, Azeddine
This paper presents an ontology-based framework for a contextual semantic representation of learning assets within a Community of Practice of E-learning (CoPE). The community, made up of actors from the e-learning domain (teachers, tutors, pedagogues, administrators...), is considered as a virtual space for exchanging and sharing techno-pedagogic knowledge and know-how between those actors. Our objective is to semantically describe the CoPE's learning assets using contextual semantic annotations. We consider two types of semantic annotations: (a) objective annotations, describing the learning assets with a set of context-related metadata and (b) subjective annotations, to express the members' experience and feedback regarding these same assets. The paper is illustrated with a case study related to a semantic adaptive wiki using the framework and aiming to foster the knowledge sharing and reuse between the CoPE's members. The wiki provides essentially a semantic search and a recommendation support of assets.